Efficacy of extracellular vesicles from dental pulp stem cells for bone regeneration in rat calvarial bone defects - Imanishi, Yuka (Inflamm Regen, 2021)
BACKGROUND: Extracellular vesicles (EVs) are known to be secreted by various cells. In particular, mesenchymal stem cell (MSC)-derived EVs (MSC-EVs) have tissue repair capacity and anti-inflammatory properties. Dental pulp stem cells (DPSCs), which are MSCs isolated from pulp tissue, are less invasive to the body than other MSCs and can be collected from young individuals. In this study, we investigated the efficacy of EVs secreted by DPSCs (DPSC-EVs) for bone formation. METHODS: DPSC-EVs were isolated from the cell culture medium of DPSCs. DPSC-EVs were unilaterally injected along with collagen (COL), beta-tricalcium phosphate (β-TCP) or hydroxyapatite (HA) into rat calvarial bone defects. The effects of DPSC-EVs were analyzed by micro-computed tomography (micro-CT) and histological observation. RESULTS: Micro-CT showed that administration of DPSC-EVs with the abovementioned scaffolds resulted in bone formation in the periphery of the defects. DPSC-EVs/COL specifically resulted in bone formation in the center of the defects. Histological observation revealed that DPSC-EVs/COL promoted new bone formation. Administration of DPSC-EVs/COL had almost the same effect on the bone defect site as transplantation of DPSCs/COL. CONCLUSIONS: These results suggest that DPSC-EVs may be effective tools for bone tissue regeneration.